Towards YMD (Y-Modulation Detection Algorithms and Devices) Applications in CryoSEM for Surface Studies of Superconductors: Per Aspera ad Astra - PL, Aleksandrov; MK, Filippov; OV, Gradov; IA, Maklakova (Annals of Mathematics and Physics, 2026)
The use of various electron microscopy techniques to study superconductors has been established since the 1980s, encompassing both high-resolution transmission electron microscopy (HRTEM) and lower magnification scanning electron microscopy (SEM). A significant challenge with these methods is the temperature dependence of imaging within the electron microscope, which necessitates noise reduction and specialized cooling systems, such as Low-Temperature Scanning Electron Microscopy (LTSEM). Programmable stages with temperature stabilization allow for analyzing temperature dependencies similar to studies on dielectric composites and semiconductors. Attempts to replace SEM and HRTEM with simpler scanning probe and tunnelling microscopy methods have not resolved the initial challenges, as they still require advanced cooling setups. The SEM benefits of scanning for large area investigations with satisfactory temporal dynamics are often overlooked. The interaction of the superconductor with the electron beam not only visualizes but can also contrast and modify samples, revealing cooperative or additive defects observable at micro- and mesoscopic levels. Therefore, it is advisable to study the charge structure of the surface of high-temperature superconductors at real temperatures. The proposed methodology involves using Y-modulated detection techniques with JEOL microscopes, applicable in both Charge Collection Scanning Electron Microscopy (CCSEM) and electronic spectroscopy methods. This approach allows for detailed 3D topographical imaging of surface charging structures/textures created by charged structures.